2016
DOI: 10.1111/cobi.12643
|View full text |Cite
|
Sign up to set email alerts
|

Complementary benefits of tourism and hunting to communal conservancies in Namibia

Abstract: Palabras Clave: accionistas, beneficios financieros, beneficios de pago en especie, conservación basada en la comunidad, prohibición de la caza, tierras comunales

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
176
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 238 publications
(183 citation statements)
references
References 37 publications
2
176
0
5
Order By: Relevance
“…Some level of harvest is usually essential because of economic reasons and the need to provide food for the growing human population. Similarly, recreational fishing and hunting are culturally important and generate substantial revenues that may be directed to conservation [76]. What harvesting strategies are likely to minimize evolutionary impacts?…”
Section: Can Harvest-induced Evolution Be Avoided?mentioning
confidence: 99%
“…Some level of harvest is usually essential because of economic reasons and the need to provide food for the growing human population. Similarly, recreational fishing and hunting are culturally important and generate substantial revenues that may be directed to conservation [76]. What harvesting strategies are likely to minimize evolutionary impacts?…”
Section: Can Harvest-induced Evolution Be Avoided?mentioning
confidence: 99%
“…The Northern Conservation Area forms a source point from which secure and well conserved wildlife species can now been seen to be moving into adjacent conservation areas (Chase & Griffin 2008, Hunter & Kerley, 1999, KAZA, 2011, Naidoo et al, 2014. Some of these currently form sinks, where animals may be exposed to higher rates of mortality from poaching incidence or managed off-take Table 10 is comprised of aerial survey data generated by the Department of Wildlife's National and regional wildlife surveys (DWNP; The figures for some species vary extensively between aerial surveys by either Chase or the DWNP (Table 10).…”
Section: Miombo/mukusi Woodlandsmentioning
confidence: 99%
“…The recent advances in our knowledge and understanding of the migratory patterns and routes of wildlife in northern Botswana (Bartlam-Brooks et al, 2011, Fynn, Chase & Roeder, 2013, Naidoo et al, 2014 have generated some much needed hard facts and precise information on the alignment of wildlife corridors across the Northern Conservation Area and highlighted the importance of these otherwise marginal areas to the viability of wildlife across the region.…”
Section: Corridorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that trophy hunting is known to create incentives for the conservation of threatened and endangered species as well as their habitats [21][22][23][24] and is considered as a market-based intervention to conservation in most countries endowed with diverse wildlife resources [25,26]. The Convention on Biological Diversity (CBD) considers conservation to be largely characterized by sustainable utilization of resources for rural development under which the trophy hunting concept falls [27,28].…”
Section: Introductionmentioning
confidence: 99%